PENDIDIKAN MULTIKULTURAL BAGI MASYARAKAT INDONESIA YANG MAJEMUK - Kamal, Muhiddinur (Institut Agama Islam Negeri Imam Bonjol Padang, 2013)
The diversity of Indonesia is a national asset which has long been considered by the founders of this nation. It is thought that being diversity is not a barrier to realize the unity of the Republic of Indonesia. However, the current state of our nation building indicates that such a spirit has declined as conflicts among the tribes lead to unlawful acts which raise the issues of tribes, tradition or race, and religion. Education as a tool to resolve problems either as a state or a nation. As a multicultural country, Indonesia is striving to horizontal conflict which may break the unity. Multicultural education is, therefore, expected to be able to resolve the national conflicts.Copyright © 2013 by Al-Talim All right reservedDOI: 10.15548/jt.v20i3.42